Analisis Ekuitas Merek dalam Membentuk Preferensi Konsumen: Studi Kasus Malikah Coffe Shop - Gadys Putria; Veri Setiawan (Jurnal Komunikasi Dialogis, 2026)
Abstract - The development of coffee-shops on campus is no longer limited to their function as a place of consumption, but also plays a role as a space for brand identity formation and social experiences for students. This study aims to analyze the brand equity of Malikah Coffee Shop UNIDA Gontor in shaping student consumer preferences. This study uses a descriptive qualitative approach with a case study method. Data collection was conducted through observation, semi-structured interviews with students as consumers, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that Malikah Coffee Shop's brand awareness is formed naturally through its proximity and intensity of use by students. Brand association is more interpreted as a functional image that represents a quiet and comfortable study space, while perceived quality is perceived mainly from the aspects of comfort and service quality. Student brand loyalty to Malikah Coffee Shop tends to be pragmatic and habit-based, so it has not yet fully developed into emotional loyalty. This study concludes that brand equity management that is in line with the character of the pesantren campus culture plays an important role in shaping consumer preferences and has the potential to increase student loyalty in sustainable manner.